Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00820
|View full text |Cite
|
Sign up to set email alerts
|

Hyphomicrobium

Abstract: Hy.pho.mi.cro' bi.um . Gr. hyphe thread; Gr. adj. micros small; Gr. masc. n. bios life; M.L. neut. n. Hyphomicrobium thread‐producing microbe. Proteobacteria / Alphaproteobacteria / Rhizobiales / Hyphomicrobiaceae / Hyphomicrobium Cells 0.3–1.2 × 1–3 µm; rod‐shaped with pointed ends, or oval, egg‐, or bean‐shaped ; produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 186 publications
0
2
0
Order By: Relevance
“…1). Denitrifying Azospira (6.51%), Haliangium (2.14%), Hyphomicrobium (0.90%), and Dechloromonas (0.23%) increased significantly, as they were able to grow on simple organic acids (Osaka et al 2006, Gliesche et al 2015, Nam et al 2016). The PAO Candidatus Accumulibacter (6.26%) were 2.3-9.5 times more abundant than those in phase I.…”
Section: Vfas Supplementation Altered Community Structure and Comammo...mentioning
confidence: 99%
“…1). Denitrifying Azospira (6.51%), Haliangium (2.14%), Hyphomicrobium (0.90%), and Dechloromonas (0.23%) increased significantly, as they were able to grow on simple organic acids (Osaka et al 2006, Gliesche et al 2015, Nam et al 2016). The PAO Candidatus Accumulibacter (6.26%) were 2.3-9.5 times more abundant than those in phase I.…”
Section: Vfas Supplementation Altered Community Structure and Comammo...mentioning
confidence: 99%
“…Preliminary experiments confirmed that DCM-degrading strain MC8b was also capable of growing with methanol, the reference growth substrate for strains of the Hyphomicrobium genus [32] to which strain MC8b had been tentatively affiliated [14]. We hypothesised that synthesis of the required dehalogenase to sustain strain MC8b growth on DCM may be regulated by the presence of its growth substrate, as observed in many dehalogenating strains [33].…”
Section: Resultsmentioning
confidence: 60%
“…In this environment, bacteria adhered to the wall surface in low energy zones (i.e., opaque bands), less susceptible to leach, where they found more stable conditions to catalyze Mn 2+ oxidation (Nealson, 2006). This hypothesis is further supported by the identification of putative predivisional cells, which are usually associated with the attachment of cells to the substrate (Gliesche et al, 2015;Hirsch and Gebers, 2015). Accordingly, the spatial distribution of the different morphotypes points to a strong influence exerted by the geometry of the substrate surface (i.e., morphology of the cave walls) on the hydraulic regime, which, in turn, controls the detrital supply and microbial colonization that trigger the formation of highly disordered vernadite, instead of todorokite and/or ranciéite.…”
Section: Significance Of Patinas Morphotypesmentioning
confidence: 83%